A Commentary on the Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care - Ventura-Junca, Patricio (Christian bioethics, 2001)
Patricio Ventura-Junca; A Commentary on the Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care, Chri